2015
DOI: 10.1117/1.jpe.5.053099
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency solar-thermophotovoltaic system equipped with a monolithic planar selective absorber/emitter

Abstract: We demonstrate a high-efficiency solar-thermophotovoltaic system (STPV) using a monolithic, planar, and spectrally selective absorber/emitter. A complete STPV system using gallium antimonide (GaSb) cells was designed and fabricated to conduct power generation tests. To produce a high-efficiency STPV, it is important to match the thermal radiation spectrum with the sensitive region of the GaSb cells. Therefore, to reach high temperatures with low incident power, a planar absorber/emitter is incorporated for con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 16 publications
(13 reference statements)
0
53
0
1
Order By: Relevance
“…Spectrally selective absorbers and emitters are key components in various energy conversion applications such as solar thermophotovoltaics (STPV), radiative cooling, solar steam generation, etc. In order to maximize the utilization of solar energy, STPV requires the cooperative spectral manipulation of a broadband solar absorber and a narrowband infrared emitter.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Spectrally selective absorbers and emitters are key components in various energy conversion applications such as solar thermophotovoltaics (STPV), radiative cooling, solar steam generation, etc. In order to maximize the utilization of solar energy, STPV requires the cooperative spectral manipulation of a broadband solar absorber and a narrowband infrared emitter.…”
mentioning
confidence: 99%
“…In addition, thanks to the narrowband emission, our HAE‐based STPV can earn 10% efficiency increment compared to the counterpart of broadband emitters (Part III, Supporting Information). Note that in a real system, the unavoidable conduction loss through the absorber/emitter's holder and the nonideal view factor of emitter would introduce extra heat loss, leading to the currently low system efficiency of no more than 10% . Our HAE‐based cage‐type STPV system can provide a feasible route to essentially increase this efficiency limit.…”
mentioning
confidence: 99%
“…Until about 2013, the reported experimental system efficiencies, in which the input power has been directly measured, were around 1% (16)(17)(18)(22)(23)(24). Then, beginning with 2015, system_exp exceeding 5% started to appear in the literature (19)(20)(21) Si-MIM structure on a tungsten substrate for the emitter (26).…”
Section: Introductionmentioning
confidence: 99%
“…An ideal STPV system has a solar-to-electric energy conversion efficiency much higher than that of a stand-alone PV cell, as a carefully designed STPV intermediate structure can fully capture the incident sunlight and convert it into narrowband thermal emission right above the bandgap of the PV cell 10 . It has been theoretically shown that the STPV efficiency could significantly surpass the aforementioned Shockley-Queisser limit, reaching 85% and 54% under fully concentrated and unconcentrated solar radiation, respectively 11 .Recently, several proof-of-concept STPV experiments have been reported employing various absorber/emitter intermediate structures [12][13][14][15][16] , including multi-walled carbon nanotubes, photonic crystals (PhCs), and two-dimensional multilayers. Although these initial demonstrations are quite…”
mentioning
confidence: 99%
“…Recently, several proof-of-concept STPV experiments have been reported employing various absorber/emitter intermediate structures [12][13][14][15][16] , including multi-walled carbon nanotubes, photonic crystals (PhCs), and two-dimensional multilayers. Although these initial demonstrations are quite…”
mentioning
confidence: 99%